Pengaruh Kemudahan Transaksi Dan Shopping Convenience Terhadap Customer Satisfaction Melalui Keputusan Pembelian Dalam Transaksi Belanja Online (Studi pada Mahasiswa FISIP Undip Pengakses Situs Lazada.co.id) - Moch Isnain Damasta; Widayanto Widayanto (Universitas Diponegoro, 2018)
Current business competition has driven the business manager for fast-moving, creative and anticipatory. This is caused by a change in the system of business competition which make use of technology in the operation of his business. This study discusses the use of the site and the online trading application Lazada.co.id. The purpose of this research is to know the influence between the ease of transactions, shopping convenience, and purchasing decisions towards customer satisfaction. The direct influence of the test results in this research is the ease of transactions, shopping convenience, and purchasing decision proved to be a significant and positive effect toward customer satisfaction. Test results of the other direct influence between the ease of transaction and shopping convenience of purchase also proved to be a positive and significant effect. Indirect influence test results between the ease of transaction against a customer satisfaction through influential buying decision is positive and significant. Whereas indirect influence test results between the shopping convenience towards customer satisfaction through purchasing decisions is also positive and significant effect. Advice to PT. Lazada Indonesia, is expected to respond to complaints from consumers, so that customer satisfaction can be improved.